The Analysis of Chief Information Officers’ Changing Roles in Enterprises - Pecko, Dejan; Bobek, Samo; Sternad Zabukovšek, Simona (Naše gospodarstvo/Our economy, 2014)
Modern business is requiring more and more business skills and ideas from Chief In- formation Officers (CIOs) in terms of how to use IT solutions to help companies achieve better and more efficient operations. Information technology is no longer just a support function; it can be used alone or in conjunction with other business proces- ses in the company to create value. Modern CIOs need to understand where and how IT can contribute to the improvement of the company and how to integrate it into achieving the company’s strategic goals. This article analyses the CIO pheno- menon and changes reported in studies.